Agroforestry paying off - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Farmer participation is giving a boost to agroforestry and, in turn, to farmer income and environmental protection. Agroforestry growing trees and crops together could be set for a bigger take-up by small-scale farmers.